Case report: dual primary malignancies treated by laparoscopic multiorgan resection with natural orifice specimen extraction surgery - Hu, Kunpeng; Ke, Yifan; Chen, Qin; Wu, Jiezhong; Ke, Yingping; Xie, Qiuxian; Liu, Bo; Chen, Jiajia (Frontiers in Oncology, 2022)
With microtrauma becoming a consensus, in order to improve surgical treatment capability, the clinical application of laparoscopic multiorgan resection is becoming more and more complicated and diversified. Recently, we successfully presented a case of transvaginal specimen extraction surgery that included laparoscopic anatomical left hemihepatectomy combined with laparoscopic total hysterectomy and bilateral adnexectomy and the pelvic and para-aortic lymphadenectomy. The patient, a 75-year-old woman, was hospitalized with abnormal vaginal discharge and bleeding. The pathologic diagnosis of uterine curettage was endometrioid adenocarcinoma. After completing examinations such as color Doppler ultrasound, CEUS, MRCP and thoracoabdominal enhanced spiral CT, preoperative diagnosis was considered as endometrial cancer and a space-occupying lesion in the liver (primary or secondary site?). No lymphatic or distant metastasis had been found. We also excluded Lynch syndrome by digestive endoscopy and gene sequencing. After a multidisciplinary consultation, the patient underwent surgery under general anesthesia on 24 September 2021. The operation was completed uneventfully in 6 hours, then the patient was transferred to the ICU for follow-up monitoring. The patient began to eat and was able to leave bed on the 4th postoperative day. According to immunohistochemistry, the patient's postoperative diagnosis was intrahepatic cholangiocarcinoma (ICC) and endometrial cancer. Compared with open surgery, laparoscopic multiorgan resection with natural orifice specimen extraction surgery (NOSES) has many advantages such as fewer traumas, shorter recovery time, and better postoperative quality of life. However, combined large-scale laparoscopic surgeries of different organs can be challenging for surgeons and anesthesiologists. No similar cases have been searched.